Special architecture and anti-wear strategies for giant panda tooth enamel: Based on wear simulation findings - Wu, Yuanheng; Liu, Jinxing; Yang, Yongqiang; Tu, Shaotong; Liu, Zichen; Wang, Yingyun; Peng, Chen; Liu, Gang; Jin, Yipeng (Frontiers in Veterinary Science, 2022)
Giant pandas are the flagship species of the world's conservation animal.Bamboo is the primary food source for giant pandas. And the extreme toughness of bamboo fiber is the most likely cause of dental wear in giant pandas. At present, the studies of tooth enamel wear in humans and some domesticated animals are relatively well established, but less research has been conducted in giant pandas. The purpose of this study was to investigate whether giant panda's tooth enamel has excellent wear resistance, and to provide a basis for better understanding of the evolution process of giant pandas. In this study, the abrasion resistance of dental enamel of giant panda was compared with that of herbivore cattle and carnivore dogs from microscopic and macroscopic perspectives, respectively, through micro scratch test and frictional wear test.. The results showed that the boundary between the enamel prism and the enamel prism stroma were well defined in giant pandas and canine teeth, while the enamel of bovine teeth appeared to be more dense. The tribological properties of giant panda enamel under constant load were similar to those of canine and differed significantly from those of bovine.. Microcratch test results showed that the microcratch depth of giant pandas and canine enamel was greater than in cattle, with greater elastic recovery occurring in dogs. Scratch morphology showed that the critical value of substantive damage to enamel was greater in pandas than in dogs and cattle. The analysis suggests that the enamel of giant pandas has a neatly arranged special structure, which may disperse extrusion stress and absorb impact energy through a series of inelastic deformation mechanisms to cope with the wear caused by eating bamboo. In this study, the excellent wear resistance of giant panda's enamel was confirmed by wear test, and a possible theoretical explanation was provided for how the special structure of giant panda's enamel could improve its wear resistance, which provided a direction for subsequent theoretical and experimental studies on giant panda's enamel and its biomaterials.